Holocene catastrophic caldera-forming eruptions of Ksudach volcano, Kamchatka - Melekestsev I.V.; Braitseva O.A.; Ponomareva V.V.; Sulerzhitskiy L.D. (1996)
Four Plinian eruptions of Ksudach have been reconstructed and dated by the carbon-14 method. The eruptions produced three collapse calderas: the KS1 eruption formed Caldera V 1700-1800 years ago, the KS2 and KS3 events produced Caldera IV 6000-6100 years ago, and the KS4 eruption formed Caldera III 8700-8800 years ago. The most violent eruption was the KS1 event. The sizes of the calderas were 4 × 6.5 km (V), 5 × 6 km (IV), and presumably 2-3 km across (III). Juvenile material was erupted in a rhythmic manner. The composition of the products was dominated by andesite (KS2 and KS4), dacite and rhyodacite (KS3), and rhyodacite (KS1). It is assumed that all caldera-forming eruptions were triggered by the injection of a new portion of high-temperature basic magma and its mixing with the cooling acid magma of the preexisting source. -from Journal summary